2008
DOI: 10.1897/07-501.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary esfenvalerate exposures on three aquatic insect species representing different functional feeding groups

Abstract: Given the chemical properties of synthetic pyrethroids, it is probable that compounds, including esfenvalerate, that enter surface waters may become incorporated into aquatic insect food sources. We examined the effect of dietary esfenvalerate uptake in aquatic insects representing different functional feeding groups. We used three field-collected aquatic insect species: A grazing scraper, Cinygmula reticulata McDunnough (Ephemeroptera: Heptageniidae); an omnivorous filter feeder, Brachycentrus americanus Bank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Preexposure of dietary items to 0.75 and 1.0 µg/L esfenvalerate for 24 hours resulted in increased rates of case-abandonment and mortality following consumption (Palmquist et al, 2008a). Although the dietary pyrethroids concentrations necessary to affect aquatic invertebrates appear to be significantly higher than aqueous concentrations, these results suggest that pyrethroids may still be toxicologically active when adsorbed to organic material.…”
Section: Effects Of Dietary Exposure To Pyrethroidsmentioning
confidence: 90%
See 2 more Smart Citations
“…Preexposure of dietary items to 0.75 and 1.0 µg/L esfenvalerate for 24 hours resulted in increased rates of case-abandonment and mortality following consumption (Palmquist et al, 2008a). Although the dietary pyrethroids concentrations necessary to affect aquatic invertebrates appear to be significantly higher than aqueous concentrations, these results suggest that pyrethroids may still be toxicologically active when adsorbed to organic material.…”
Section: Effects Of Dietary Exposure To Pyrethroidsmentioning
confidence: 90%
“…After three weeks, mayfly nymphs (Cinygmula reticulata) fed on algae pre-exposed for 24-hours to 0.5 to 1.0 µg/L esfenvalerate were smaller than control organisms. Further, consumption of diet exposed to 1.0 µg/L esfenvalerate for 10 days by final instar C. reticulata nymphs reduced the number and length of eggs in emerged females (Palmquist et al, 2008a).…”
Section: Effects Of Dietary Exposure To Pyrethroidsmentioning
confidence: 94%
See 1 more Smart Citation
“…141) Brachycentrus americanus (caddisfly) and Cinygmula reticulata (mayfly) fed on esfenvalerate-treated algal cultures showed increasing mortality with case abandonment and growth inhibition with lower egg production, respectively, clearly indicating the dietary uptake of the insecticide. In contrast, when esfenvalerate-treated C. tentans larvae were fed to Hesperoperla pacifica (stonefly), no significant toxic effects were observed without a prey rejection, most likely due to the rapid metabolism of the insecticide.…”
Section: )mentioning
confidence: 99%
“…Though adsorption of pyrethroids to POM may reduce cutaneous exposure to aquatic invertebrates, results suggest that dietary exposure may still be an issue. In a study of dietary exposure of esfenvalerate to three aquatic invertebrates from different phylogenetic groups, Cinygmula reticulata (grazing scraper, Mayfly), Brachycentrus americanus (omnivorous filter feeder, Caddis fly), and Hesperoperla pacifica (predator, Stonefly); Palmquist et al (2008) found that not only did lethal and sub-lethal effects from dietary exposure occur, but also that there was no indication that animals avoided contaminated food. It has been estimated that daphnids consume an average of 84,000 cells of algae daily, depending on the species (Infante and Litt 1985).…”
Section: Discussionmentioning
confidence: 99%